The beginnings of the natural history museology in Europe - Chervonenko, O. V.; Kepin, D. V. (History of science and technology, 2016)
The paper deals with the history of development of views on the nature during the ancient era as well as the beginnings of museum studies in the context of creation natural history collections in Europe during classical antiquity. Based on the results of analysis of archeological evidences and historical documents it was revealed that institutions called “mouseion” (lat. thesaurus) common in both Ancient Greece and Rome cannot be equated with museums in the modern sense of the term. The establishment of museums as sociocultural institutions and the creation of natural history exhibitions in European countries were held during the Renaissance and the Age of Enlightenment and were related with major discoveries in the field of biology.